Pengaruh Model Pembelajaran Kooporatif Tipe Student Teams Achievement Division (STAD) Terhadap Peningkatan Minat Belajar Siswa - Evi Djumiati; Ria Herdhiana; Bella Anantha Sritumini (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2017)
This research is in the background of the lack of student interest in economic subjects caused by rarely the presence of a teacher in teaching learning, is also found in the learning process in the classroom which only use the usual learning used by teachers, where the learning activities are still centered on the teacher, and there is no interaction in involving students resulting class becomes monotonous and lead to a lack of interest in learning the economic lesson. This research entitled "The Influence of Cooperative Learning Model Type Student Team Achievement Division (STAD) Against Increasing Student Learning Interest". The test of this research is to know the influence of cooperative learning model of Student Team Achievement Division (STAD) to increase student interest in learning. The research used is pre-test-Post-test Nonequivalent Control Group Design. The population in this research is the students of class XI IPS SMAN 21 BANDUNG as many as 106 students and the sample in this research is class XI IPS 2 And XI IPS 1 where the class as experiment class and control class. The data were collected by using questionnaires used to collect student interest in experiment and control class. Based on the result of data analysis, it can be concluded that there is influence of cooperative learning model of Student Team Achievemen Division (STAD) type toward the increasing of student's interest in economic subject at SMA Negeri 21 Bandung.